2020
DOI: 10.1080/1359432x.2020.1843533
|View full text |Cite
|
Sign up to set email alerts
|

Working, but not for a living: a longitudinal study on the psychological consequences of economic vulnerability among German employees

Abstract: Despite the rise of in-work poverty across Europe, the psychological consequences of individual economic vulnerability are still rather unknown. Drawing on both objective and subjective conceptualizations of economic vulnerability, we investigate the effects of individual low labour income and perceived financial strain on mental well-being. We argue that economic vulnerability restricts workers' agency and propose sense of control as a mediator in the relationship between economic vulnerability and mental wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 115 publications
(189 reference statements)
1
8
0
1
Order By: Relevance
“…These findings are in line with previous studies that found robust differences in health between precarious and nonprecarious employees (Benach et al 2014) and only a weak causal interplay between precarious employment and health within employees (Dawson et al 2015; Green and Heywood 2011; Klug et al 2020; Pförtner and Schmidt-Catran 2017). For example, the study by Pförtner and Schmidt-Catran (2017) shows with data from the GSOEP from 1995 to 2013 that variations in self-rated health are largely explained by differences between working poor employees and non-working poor employees and not by changes in an employed individual’s working poverty status.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are in line with previous studies that found robust differences in health between precarious and nonprecarious employees (Benach et al 2014) and only a weak causal interplay between precarious employment and health within employees (Dawson et al 2015; Green and Heywood 2011; Klug et al 2020; Pförtner and Schmidt-Catran 2017). For example, the study by Pförtner and Schmidt-Catran (2017) shows with data from the GSOEP from 1995 to 2013 that variations in self-rated health are largely explained by differences between working poor employees and non-working poor employees and not by changes in an employed individual’s working poverty status.…”
Section: Discussionsupporting
confidence: 93%
“…Longitudinal studies, although less common in the literature given their requirements and complexities, are better suited for producing knowledge about cumulative risk over time than cross-sectional observational studies (Ferrie et al 2002; Scott-Marshall and Tompa 2011). Still, most of the extant knowledge about longitudinal associations between precarious employment and subsequent health status is based on differences between precarious and nonprecarious workers rather than intraindividual changes in precarious employment status and health (Dawson et al 2015; Green and Heywood 2011; Klug et al 2020; Pförtner and Schmidt-Catran 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(e.g., Debus et al, 2012; Kessler & Gutworth, online first-2022; Naranjo et al, 2021; Okulicz-Kozaryn, 2011; Probst & Jiang, 2017; Shultz, Wang, Crimmins, et al, 2010)• What does the data suggest about the magnitude of an effect, base rate, role of time (within-person time or historical time), or level of analysis at which an effect emerges? (e.g., Klug et al, 2020; Shoss & Kueny, 2022)• How does public policy or other events influence an effect? (e.g., Probst et al, 2020; Sieweke & Santoni, 2020)…”
Section: Archival Data Sets Should Not Be a Secondary (Or Even Last) ...mentioning
confidence: 99%
“…• What does the data suggest about the magnitude of an effect, base rate, role of time (within-person time or historical time), or level of analysis at which an effect emerges? (e.g., Klug et al, 2020; Shoss & Kueny, 2022)…”
Section: Archival Data Sets Should Not Be a Secondary (Or Even Last) ...mentioning
confidence: 99%